Nightfall [large type] - Wright, Richard B. (Richard Bruce), 1937-2017 (Center Point Large Print, 2016)
"Retired university professor James Hillyer barely exists after the death of his beloved daughter in her forties. He locates the woman he fell in love with many years ago on a summer trip to Quebec, but Odette's present existence is haunted by ghosts from her own past. The collision of past and present alters their lives"--